Design and fabrication of reduced graphene oxide (RGO) incorporated NiCo2S4 hybrid composites as electrode materials for high performance supercapacitors - A. Jafar Ahamed; P. Kanagambal (Chemical Physics Impact)
One of the most promising bimetallic sulphides for use in energy-storage systems is NiCo2S4, but further research is required to give it a high reversibility and electrochemical reaction capacity. In this study, we show the rational materials design of an ideal NiCo2S4 nanoparticle as a NiCo2S4/RGO nanocomposite, embedded in a reduced graphene oxide (RGO) matrix. NiCo2S4 nanoparticles, which ranged in size from 20 to 25 nm and were firmly fixed on the surface of RGO sheets, made up the produced composite. As predicted, the produced nanocomposite displayed a high specific surface area, a mesoporous structure, and high conductivity, resulting in a large electroactive area and rapid electron and ion motion. Additionally, we present the advancements in material science, showcasing the NiCo2S4/RGO nanocomposite electrode, which has a long cycle life of 5000 cycles, a high capacitance retention of 85.6 %, and an exceptional specific capacitance of 1505 Fg-1 at 1 Ag-1. A high active-material loading asymmetric supercapacitor serves as an example of the real-world use. The NiCo2S4/RGO nanocomposite exhibits an exceptional 48 Whkg-1 energy density at a power density of 985 Whkg-1, while maintaining a high power density of 7227 Wkg-1 density of 25 Whkg-1. The exceptional stability and electrochemical efficiency of the NiCo2S4/RGO nanocomposite validate that our methodical materials science and technology optimisation in the areas of active substance synthesis, electrode expansion, and device design/fabrication will help advance the development of high-performance supercapacitors in future years.